1999
DOI: 10.1016/s0014-5793(99)00552-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of a drug‐resistant mutant of stress‐activated protein kinase 2a/p38 to validate the in vivo specificity of SB 203580

Abstract: Stress-activated protein kinase 2a, also called p38, is inhibited by SB 203580 and this drug has been used widely to implicate this enzyme in the regulation of many physiological processes. Here, we introduce a novel method of general application, which can be used to establish whether the effects of SB 203580 are mediated via inhibition of stress-activated protein kinase 2a/p38 or whether they result from`non-specific' effects. Four events thought to occur upon activation of stressactivated protein kinase 2a/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 23 publications
(53 reference statements)
4
90
0
1
Order By: Relevance
“…To determine whether these agents also inhibit p38 signaling in intact cells, we monitored their effects on phosphorylation of the transcription factor cAMP-response element binder (CREB), a downstream effector of p38. Phosphorylation of CREB induced by insulin, fibroblast growth factor, or ultraviolet radiation is abrogated by pretreating cells with 10 M SB203580 (14,45,46). Ultraviolet radiation-induced CREB phosphorylation is inhibited by SB203580 in cells expressing wild type p38 but not in cells expressing an SB203580-resistant p38 mutant, confirming that CREB phosphorylation is p38-dependent (46).…”
Section: Inhibition Of P38 Kinase Activity By the Novel Compoundsmentioning
confidence: 87%
See 1 more Smart Citation
“…To determine whether these agents also inhibit p38 signaling in intact cells, we monitored their effects on phosphorylation of the transcription factor cAMP-response element binder (CREB), a downstream effector of p38. Phosphorylation of CREB induced by insulin, fibroblast growth factor, or ultraviolet radiation is abrogated by pretreating cells with 10 M SB203580 (14,45,46). Ultraviolet radiation-induced CREB phosphorylation is inhibited by SB203580 in cells expressing wild type p38 but not in cells expressing an SB203580-resistant p38 mutant, confirming that CREB phosphorylation is p38-dependent (46).…”
Section: Inhibition Of P38 Kinase Activity By the Novel Compoundsmentioning
confidence: 87%
“…The p38AGF mutant has been used previously to study the functional role of p38 in cells in culture and in mice (33)(34)(35)46). Expression of p38AGF was induced after 3T3-L1 cells differentiated into adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a chemical genetic approach first described in vitro (12,13) has been employed in mice in which Thr 106 in p38␣ was substituted with a more bulky methionine, disrupting the hydrophobic groove on which many inhibitors depend for binding (8). We have made use of these mice to address the uncertainties highlighted above.…”
mentioning
confidence: 99%
“…In cell types such as macrophages, which only express p38␣ and not the other SB 203580-sensitive isoform, p38␤ (44), it can also be concluded that the critical activity in the phenomenon under study was that of p38␣. Expression of an SB 203580-resistant mutant of p38 MAPK was used to demonstrate that the inhibitory effect of SB 203580 on activation of MAPKAP kinase-2 and mitogen-and stress-activated protein kinase-1 involved inhibition of p38 MAPK but that the ability of SB 203580 to activate Raf-1 did not (45).…”
mentioning
confidence: 99%